2002
DOI: 10.1128/jvi.76.5.2518-2528.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Glycoproteins Induce Global Surface Protein Down-Modulation and Loss of Cell Adherence

Abstract: The Ebola virus envelope glycoprotein (GP) derived from the pathogenic Zaire subtype mediates cell rounding and detachment from the extracellular matrix in 293T cells. In this study we provide evidence that GPs from the other pathogenic subtypes, Sudan and Côte d'Ivoire, as well as from Reston, a strain thought to be nonpathogenic in humans, also induced cell rounding, albeit at lower levels than Zaire GP. Sequential removal of regions of potential O-linked glycosylation at the C terminus of GP1 led to a step-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
223
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(239 citation statements)
references
References 46 publications
13
223
1
Order By: Relevance
“…We next sought to determine the contribution of the highly glycosylated mucin domain to the antitetherin activity of Ebola GP. The mucin domain within GP is known to contribute to cellular pathogenesis by affecting surface levels of a variety of cellular proteins (14,15). It appears that this region of GP, however, is not required to counteract tetherin because deletion of the mucin domain had no effect upon the ability of GP to promote virion release from tetherin-expressing cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to determine the contribution of the highly glycosylated mucin domain to the antitetherin activity of Ebola GP. The mucin domain within GP is known to contribute to cellular pathogenesis by affecting surface levels of a variety of cellular proteins (14,15). It appears that this region of GP, however, is not required to counteract tetherin because deletion of the mucin domain had no effect upon the ability of GP to promote virion release from tetherin-expressing cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An extremely divergent mucin-like region is localized to the C-terminal region of GP1. Several groups have previously shown that the GP mucin domain causes downmodulation of cell surface proteins (14,15). Therefore, we initially hypothesized that the mucin domain within Ebola GP would prove critical in interfering with tetherin activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the interaction between b1-integrin and GP was shown to contribute to the loss of adhesion of GP-expressing cells 7,24 . Furthermore, a role for the GP 2 subunit in counteracting interferon-induced antiviral response via the protein tetherin (BST-2) has been proposed 25 .…”
mentioning
confidence: 99%
“…The dysregulation of the immune response and a heavy inflammatory reaction, described as a 'cytokine storm', are induced on EBOV infection 5 . Whether the detachment of infected endothelial cells and the concomitant leakage of the endothelial barrier are important factors in the pathogenesis of Ebola virus disease remains controversial [6][7][8][9][10][11] . Among other factors, the cytotoxicity of EBOV has been attributed to the envelope glycoprotein (GP) 6 ; however, the molecular mechanism underlying the pathogenicity of this virus is unclear.…”
mentioning
confidence: 99%
“…Both may create a concern with respect to biosafety. The first strategy relies on viral glycoproteins, which may be toxic in vivo 99,100 and thus the next necessary step will be to mutate them in order for the system to be safer. 56 The second strategy may be not compatible with the CF environment and be more deleterious than expected.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%